2023
DOI: 10.3389/fmech.2023.1185231
|View full text |Cite
|
Sign up to set email alerts
|

A critical review of experimental analyses performed on animals, post-mortem human subjects, and substitutes to explore primary blast-induced Traumatic Brain Injuries

Natacha Elster,
Johanna Boutillier,
Pascal Magnan
et al.

Abstract: Although blast-induced Traumatic Brain Injury (bTBI) has become a signature wound of conflict, its cause is not yet fully understood. Regarding primary blast injuries, i.e., those caused by the propagation of shock waves in the body, four direct and two indirect injury mechanisms have been mainly proposed in the literature. Since numerous authors have exposed instrumented animals, Post-Mortem Human Subjects (PMHS), and head substitutes to blast conditions, the aim of this review is to classify them in terms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
(174 reference statements)
0
2
0
Order By: Relevance
“…Rather, it is a broad overview of the present state of knowledge in each subdomain. For a few subdomains, review articles 51 , 52 , 89 , 100 , 146 , 168 , 212 , 213 are already available in the literature. Nonetheless, we have extensively gone through the literature in each subdomain.…”
Section: Transparency Rigor and Reproducibility Summarymentioning
confidence: 99%
“…Rather, it is a broad overview of the present state of knowledge in each subdomain. For a few subdomains, review articles 51 , 52 , 89 , 100 , 146 , 168 , 212 , 213 are already available in the literature. Nonetheless, we have extensively gone through the literature in each subdomain.…”
Section: Transparency Rigor and Reproducibility Summarymentioning
confidence: 99%
“…Several metrics of interest were collected such as the time of wave arrival, the first peak values of the internal pressures and the shell strains, as well as the extreme values. Results showed that internal pressures and shell strains are related; however, only timedomain analyses were performed in those mentioned studies (Elster et al, 2023). Since the time history of quasi-ideal blast waves could be approximated by pulse signals with broad frequency spectra, it would be interesting to analyze blast related results in the frequency domain as well.…”
Section: Introductionmentioning
confidence: 99%